The Presidential Threshold As An Open Legal Policy In General Elections In Indonesia - Mas’udah, Al (Prophetic Law Review, 2020)
This paper aims to examine the implementation of the legal policy on presidential threshold in Indonesia after the stipulation of The Fourth Amendment of the Constitution of 1945. The stipulation of the presidential threshold based on the Constitutional Court ruling Number 14 / PUUXI / 2013 triggered fierce controversies. As a result, the function of the 2014 legislative election as the threshold for the requirements of presidential candidacy for 2019 general election becomes no longer relevant and applicable. This is a normative legal research, which concludes that it is necessary to make laws about the provision of general election, reorganization of election management institutions, and the preparation of election logistics.Keywords: Constitution, General Election, Presidential ThresholdPresidensial Threshold Sebagai Open Legal Policy Dalam Pemilihan Umum Di IndonesiaAbstrakTulisan ini bertujuan untuk mengkaji implementasi politik hukum mengenai presidensial threshold di Indonesia pasca ditetapkannya Perubahan Keempat UUD NRI 1945. Penetapan presidensial threshold berdasarkan putusan MK Nomor 14/PUUXI/2013 memicu kontroversi sengit. Akibatnya, fungsi Pemilu Legislatif 2014 sebagai ambang batas persyaratan pencalonan presiden pada Pemilu 2019 menjadi tidak relevan dan aplikatif lagi. Penelitian ini merupakan penelitian hukum normatif yang menyimpulkan perlunya pembuatan undang-undang tentang penyelenggaraan pemilu, reorganisasi lembaga penyelenggara pemilu, dan penyiapan logistik pemilu.Kata kunci: Konstitusi, Pemilihan Umum, Presidensial Threshold